THE RELATIONSHIP OF PARENT GUIDANCE WITH CHILDREN'S LEARNING RESPONSIBILITY AT BINA SATRIA MULIA MIDDLE SCHOOL MEDAN DELI DISTRICT - Indri Sari; Lahmuddin Lubis; Erni Suyani (Universitas Dharmawangsa, 2023)
This study aims to: (1) To find out how the guidance of parents towards children's learning responsibilities at Bina Satria Mulia Middle School, Medan Deli District; (2) To find out the relationship of parental guidance to children's learning responsibilities at Bina Satria Mulia Middle School, Medan Deli District and (3) To find out the barriers to parental guidance on children's learning responsibilities at Bina Satria Mulia Middle School, Medan Deli District. The type of research used in this study is quantitative research, this study uses an ex post facto design because the independent variables are not given certain treatment and are not controlled.The results showed that: (1) Parental guidance at Bina Satria Mulia Middle School, Medan Deli (a) parents really care about their children; (b) cooperation between parents and the school. (2) The relationship between parental guidance at Bina Satria Mulia Middle School, Medan Deli (a) Invite parents to school; (b) Hold meetings regarding student cases. (3) Barriers to parental guidance at Bina Satria Mulia Middle School, Medan Deli (a) children have difficulty understanding the teacher's explanation; (b) children have difficulty in getting literature books